Security sliding mode control for networked control system under multi‐channel Markovian hybrid cyber‐attacks - Mao, Dancheng; Niu, Yugang; Li, Jiarui; Yang, Yekai (International journal of robust and nonlinear control, 2024)
This work investigates the security sliding mode control problem of uncertain discrete‐time systems under an unreliable network, in which denial of service and deception attacks may randomly occur in each sensor‐to‐controller channel. Two 2‐valued variables are introduced to model the available state signals for the controller side under random attacks. Meanwhile, by means of mapping rule, n$$ n $$ independent Markov chains are reformulated into a new Markov chain. And then, a hybrid‐attack‐probability dependent sliding function is constructed, and a desirable sliding mode controller is designed by adopting compensation strategy and available state signals. Moreover, sufficient conditions are derived, under which the closed‐loop system achieve stochastic stability along a quasi sliding mode. Moreover, a cone complementarity linearization (CCL)‐based iterative solving algorithm is proposed. Finally, simulation results are provided to verify the proposed security control approach.